2022
DOI: 10.1111/ijn.13050
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, reasons, correlates and predictors of missed nursing care in Turkey: A multi‐hospital cross‐sectional study

Abstract: Aim: We aimed to examine the frequency, reasons, correlates and predictors of missed nursing care in Turkey.Methods: This descriptive and cross-sectional study sample consisted of 1310 nurses working in inpatient units of 10 public, university and private hospitals in Istanbul.Data were collected using the Nursing Teamwork Survey-Turkish and the MISSCARE Survey-Turkish between February and June 2019. Descriptive analysis, parametric comparative analysis, correlational analysis and regression analysis were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Limited studies, to the best of the authors' knowledge, have delved into this relationship from the standpoint of registered nurses. These investigations showed that an increase in teamwork scores was correlated with a decrease in unfinished nursing care estimates [7,10,11,34].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Limited studies, to the best of the authors' knowledge, have delved into this relationship from the standpoint of registered nurses. These investigations showed that an increase in teamwork scores was correlated with a decrease in unfinished nursing care estimates [7,10,11,34].…”
Section: Discussionmentioning
confidence: 97%
“…In the international arena, teamwork has been a predictive factor for rationed nursing care estimates. The overall NTS score accounted for between 16.0 and 24.0 percent of the variance in rationed nursing care [11,34]. Additionally, higher teamwork scores were associated with redu-ced estimates of rationed nursing care in acute care settings [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Missed nursing care is a common problem worldwide. A cross-sectional study including 1,310 nurses in Turkey revealed that the mean score of missed nursing care was 2.93 on a scale of 1–4, indicating a high level of missed nursing care [ 4 ]. In Malaysia and Iran, the overall scores of missed nursing care were 1.88 and 2.57, respectively, on a scale of 1–5 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Missed nursing care (MNC), also known as unfinished nursing care, is considered a key health care delivery issue worldwide 1–3. MNC is defined as any element of patient care that is required but either left undone or considerably delayed 4.…”
mentioning
confidence: 99%